Adenovirus Infection in a Kidney–Pancreatic Transplant Recipient: Case Report - Damas, J (2023)
Adenovirus infection in transplant recipients may present from asymptomatic viremia to multisystemic involvement. Most frequently, it occurs in the first year after a kidney transplant, and it is secondary to the reactivation of latent disease. However, primary infection may occur, and disseminated disease is more common when related to primary infection. Kidney involvement may be confirmed by biopsy, although diagnosis may be presumptive. Reduction of immunosuppression and supportive care are important components of therapy. CASE DESCRIPTION: A 41-year-old female renal-pancreatic recipient 12 years before with chronic renal graft dysfunction and a functional pancreatic graft had a history of cytomegalovirus and polyoma virus infection 2 years after transplantation. She was taking tacrolimus, mycophenolate mofetil, and prednisolone. The patient was admitted after persistent uncharacteristic diarrhea 3 weeks before hospitalization without any relevant epidemiologic context. She was dehydrated, and the lab results showed worsened kidney function and leucocytosis. The viral culture revealed adenovirus. Vigorous hydration was implemented, and the mycophenolate mofetil dose was reduced. The patient was discharged, and renal function returned to previous values. DISCUSSION AND CONCLUSION: Adenovirus infection has a wide clinical presentation, and multisystemic involvement may occur in transplant recipients. Supportive care is paramount. The clinical features and viral culture confirm the diagnosis, although tissue samples and quantitative polymerase chain reaction may be required in more severe cases.